Mechanisms of ranibizumab as an anti-scarring agent in trabeculectomy / Siti Munirah Md Noh - Md Noh, Siti Munirah (Institute of Graduate Studies, UiTM, 2018)
Trabeculectomy is the gold standard procedure performed in glaucoma when topical medication and laser intervention fail to maintain the ideal intraocular pressure (IOP) of patient’s eye. However, excessive accumulation of extracellular matrix components (ECM) mediated by Tenon’s fibroblast (HTF) leads to significant cases of surgical failure. Anti-vascular endothelial growth factor (VEGF) has become the focus in current scar modulation strategy. Improved bleb morphology following trabeculectomy augmented with ranibizumab has been reported. However, mechanism of actions of ranibizumab on HTF is not well understood. Therefore, this in vitro study was conducted to elucidate mechanism of actions of ranibizumab on HTF. HTF used in this study were propagated from Tenon’s capsule obtained from patients undergoing trabeculectomy. Firstly, isolated and characterized HTF were treated with different concentrations of ranibizumab in serum and serum-free media for 24 and 48 hours and then HTF viability was measured using MTT assay. Then, HTF were extracted to measure the expression of collagen Type 1 (COL1A1), fibronectin (FN), transforming growth factor-β1 and -β2 (TGF-β1 &TGF-β2) using qRT-PCR and ELISA. The experiment was followed with metabolomics profiling which was performed to identify the most significant metabolite regulated by ranibizumab…